Analisis Sistem Pengelolaan UMKM Keripik Kedelai Dusun Sawahan Desa Pugeran Kabupaten Mojokerto - Sofiana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The village of Pugeran is one of the agraric villages where the majority of its inhabitants work as farmers because of the area that is mostly sawah. This village has great potential because most of its residents work as the entrepreneurs of UMKM Keripik Kedelai. This research was carried out with the aim of analyzing and understanding the management system of Pugeran Village management potential. This type of research is qualitative using the method of narrative inquiry. This method requires the researcher to undertake an effort to understand the dialogue or narrative obtained from the source or informant with the aim of obtaining an elaborate, in-depth, and detailed explanation. The results of this research found that the potential of Pugeran Village was well managed by BUMDes or the Village Owned Enterprise and obtained a good support facility, namely KUD or Village Unit Cooperation. (planning, organizing, actuating, dan controlling).